THE IMPLEMENTATION OF DISCOVERY LEARNING TO IMPROVE CRITICAL THINKING SKILLS AND LEARNING OUTCOMES OF STUDENTS IN CLASS VIIE SMPN 29 SEMARANG - Bagus Wicaksono, Rudy; Rahmawati, Naillysa; Budi Astuti, Cahyaning; Sunarto, Sunarto (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
This research employed a Classroom Action Research approach to enhance critical thinking abilities and student learning outcomes regarding the historical development of Pancasila. This was achieved through a discovery learning model, assisted by Kalpancas Media and Blooket, in Class VII-E of SMP Negeri 29 Semarang. The success of this classroom action research was evaluated using several performance indicators. (1) The mean value of students' knowledge of their ability to play Blooket is at least good, with a daily assessment of at least 80; (2) The mean student attitude score is at least good; (3) The mean student skill score is at least 80; and (4) The mean student learning achievement standard is at least 78, with an average classical learning completion score of 80%. The results of the research demonstrate that students' critical thinking skills, as evidenced by the formative assessment results in the areas of knowledge (assignments), attitudes, and skills, as well as their performance in the Blooket game during Cycle I, exhibited an average of 76.47. This value increased to 90 in Cycle II. The mean score for this item was 58. In the attitude aspect, the mean score in Cycle I was 60.29, which increased to 83.82 in Cycle II. Subsequently, the skill aspect was evaluated. In cycle I, the average was 81.25, and in cycle II, there was an increase of 88.33. In contrast, the mean scores for Blooket in Cycle I were 70, with an increase to 81.17 in Cycle II. In contrast, the pre-cycle student learning outcomes demonstrated a relatively low level of completeness, with only 41.17% (14 children) achieving this outcome. Subsequently, there was an increase of 73.53% (25 children) in Cycle I. In Cycle II, there was an increase of 85.30% (29 children). Consequently, there was an enhancement in both critical thinking abilities and academic outcomes among students enrolled in VII-E at SMP Negeri 29 Semarang. Keywords: Critical Thinking Skills, Learning Outcomes, Discovery Learning, Kalpancas, Combination, and Blooket.